Comparative Study Of Agitation Rate And Stationary Phase For The Removal Of Cu2+ By A.Lentulus - SHIPRA JHA; DR S.N DIKSHIT; DR G PANDEY (International Journal of Pharma and Bio Sciences, 2011)
The aim of this research work was to find out the effect of agitation rate for the removal of Cu2+.Experiments were performed under shaking and stationary conditions towards optimizing the rate for efficient Cu2+ removal by the immobilized fungal strain. Increase in agitation rate from 100-180 rpm resulted into higher copper removal.